Криміналістична характеристика злочинів проти громадської безпеки, учинених на території проведення операції Об’єднаних сил - Савчук, Т. І.; Savchuk, T. I.; ORCID: http://orcid.org/0000-0001-8024-5136; Безсонна, Т. Ф.; Bezsonna, T. F.; ORCID: http://orcid.org/0000-0002-2482-9564 (Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2019. – Вип. 1 (85). – С. 266-274, 2019)
У статті на основі аналізу слідчої та судової практики розроблено криміналістичну характеристику злочинів проти громадської безпеки, учинених на території проведення операції Об’єднаних сил. Виділено найбільш розповсюджувані злочини проти громадської безпеки, що вчиняються на території проведення операції Об’єднаних сил. Визначено структуру криміналістичної характеристики злочинів проти громадської безпеки, учинених на території проведення операції Об’єднаних сил, та проаналізовано її елементи.

The article analyzes the scientific opinions of criminologists on the concept and structure of forensic characteristics of crimes. It has been determined that the forensic characteristic is a systematic information about the features of a particular type of crime or elements of the mechanism of its commission, and reflects the logical connections between such elements and serves for the advancement of forensic versions and solving the tasks of the investigation. The content of forensic characteristics of one or another type of crime is data on specific elements of the mechanism of the crime. It is emphasized that all elements of the forensic character of the crime are interdependent and there are regular relationships that must be taken into account when they are studied. It is determined that when constructing forensic characteristics of a particular type of crime, one must take into account not only the general structure of forensic characteristics, but also the characteristic features of a specific type of crime. The most widespread crimes against public security committed on the territory of the operation of the united forces are allocated. On the basis of the analysis of investigative and judicial practice, a forensic description of crimes against public safety developed in the area of the operation of the combined forces was developed. The structure of the forensic characterization of crimes against public security committed on the territory of the operation of the combined forces was determined. It should include data on the methods of crime, the identity of the offender and the victim, the circumstances of the commission of crimes (time, place and circumstances), typical traces of the crime. The main elements of forensic characteristics of these crimes are analyzed.

В статье на основе анализа следственной и судебной практики разработана криминалистическая характеристика преступлений против общественной безопасности, совершенных на территории проведения операции Объединенных сил. Выделены наиболее распространяемые преступления против общественной безопасности, совершаемые на территории проведения операции Объединенных сил. Определена структура криминалистической характеристики преступлений против общественной безопасности, совершенных на территории проведения операции Объединенных сил, и проанализированы ее элементы.
Forensic Characteristics of Crimes against Public Safety Committed on the Territory of the Joint Forces Operation
Криминалистическая характеристика преступлений против общественной безопасности, совершенных на территории проведения операции Объединенных сил
Савчук Т. І. Криміналістична характеристика злочинів проти громадської безпеки, учинених на території проведення операції Об’єднаних сил / Савчук Т. І., Безсонна Т. Ф. // Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2019. – Вип. 1 (85). – С. 266-274.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична характеристика; злочини проти громадської безпеки; операція Об’єднаних сил; район проведення операції Об’єднаних сил; зона АТО; forensic characteristics; crimes against public safety; operation of United Forces; area of operation of United Forces; криминалистическая характеристика; преступления против общественной безопасности; операция Объединенных сил; район проведения операции Объединенных сил